Lethal hyperammonemia in a CAR-T cell recipient due to Ureaplasma pneumonia: a case report of a unique severe complication. Issue 7 (8th July 2021) - Tawfik, Pierre; Arndt, Patrick
Abstract : We report the first incidence of Ureaplasma infection causing lethal hyperammonemia in a chimeric receptor antigen T cell (CAR-T) recipient. A 53-year-old woman, after receiving CAR-T therapy, suffered sepsis and encephalopathy. She was found to have hyperammonemia up to 643 µmol/L. Imaging revealed lung consolidations and bronchoalveolar lavage PCR was positive for U. parvum . Workup excluded liver failure and metabolic abnormalities. Antibiotics, lactulose, dextrose, arginine, levocarnitine, sodium phenylbutyrate and dialysis were used. Despite these, the patient suffered persistent elevations in ammonia, status epilepticus and cerebral oedema. Early recognition of this rare infection in susceptible populations is needed. CAR-T patients are at risk due to their immunocompromised state and may have amplified harm due to the impact of CAR-T therapy on astrocytes. An early aggressive multimodality approach is needed given the high mortality rates. These include antimicrobials, possibly with double coverage for Ureaplasma . Additionally, concurrent ammonia-suppressing and ammonia-eliminating treatments are necessary.